Epiphytic PGPB Bacillus megaterium AFI1 and Paenibacillus nicotianae AFI2 Improve Wheat Growth and Antioxidant Status under Ni Stress - Veronika N. Pishchik; Polina S. Filippova; Galina V. Mirskaya; Yuriy V. Khomyakov; Vitaliy E. Vertebny; Viktoriya I. Dubovitskaya; Yuliya V. Ostankova; Aleksandr V. Semenov; Debasis Chakrabarty; Evgeny V. Zuev; Vladimir K. Chebotar (Plants, 2021)
The present study demonstrates the Ni toxicity-ameliorating and growth-promoting abilities of two different bacterial isolates when applied to wheat (Triticum aestivum L.) as the host plant. Two bacterial strains tolerant to Ni stress were isolated from wheat seeds and selected based on their ability to improve the germination of wheat plants; they were identified as Bacillus megaterium AFI1 and Paenibacillus nicotianae AFI2. The protective effects of these epiphytic bacteria against Ni stress were studied in model experiments with two wheat cultivars: Ni stress-tolerant Leningradskaya 6 and susceptible Chinese spring. When these isolates were used as the inoculants applied to Ni-treated wheat plants, the growth parameters and the levels of photosynthetic pigments of the two wheat cultivars both under normal and Ni-stress conditions were increased, though B. megaterium AFI1 had a more pronounced ameliorative effect on the Ni contents in plant tissues due to its synthesis of siderophores. Over the 10 days of Ni exposure, the plant growth promotion bacteria (PGPB) significantly reduced the lipid peroxidation (LPO), ascorbate peroxidase (APX), superoxide dismutase (SOD) activities and proline content in the leaves of both wheat cultivars. The PGPB also increased peroxidase (POX) activity and the levels of chlorophyll a, chlorophyll b, and carotenoids in the wheat leaves. It was concluded that B. megaterium AFI1 is an ideal candidate for bioremediation and wheat growth promotion against Ni-induced oxidative stress, as it increases photosynthetic pigment contents, induces the antioxidant defense system, and lowers Ni metal uptake.